Cytogenetic clonal evolution in myelodysplastic syndromes is associated with inferior prognosis. Issue 23 (26th July 2017) - Neukirchen, Judith; Lauseker, Michael; Hildebrandt, Barbara; Nolting, Ann‐Christin; Kaivers, Jennifer; Kobbe, Guido; Gattermann, Norbert; Haas, Rainer; Germing, Ulrich
Abstract : BACKGROUND: The karyotype of bone marrow cells at the time of diagnosis is a strong prognostic parameter for overall survival as well as acute myeloid leukemia (AML) progression in patients with myelodysplastic syndromes (MDS). However, to the authors' knowledge, few data exist regarding the prognostic impact of cytogenetic clonal evolution during the course of MDS. METHODS: The authors evaluated follow‐up karyotype analyses in 549 patients from the Dusseldorf MDS Registry. RESULTS: Clonal evolution was detectable in 24% of the entire cohort and in 18% of 294 patients receiving best supportive care. The authors noted a clear adverse effect of clonal evolution on the risk of leukemic transformation (hazard ratio, 2.233; P = .036) and overall survival (hazard ratio, 3.677; P <.001). The authors also analyzed the prognostic influence of subclones detectable at the time of diagnosis. Again, such a finding was associated with a significantly shorter overall survival and a higher 5‐year‐probability of acute myeloid leukemia progression (30% vs 22%). CONCLUSIONS: The results of the current study support the belief that follow‐up karyotype analyses should be performed, especially in patients with lower‐risk and intermediate‐risk MDS, to identify those patients who are at higher risk of disease progression and therefore might benefit from earlier or more intensive treatment. Cancer 2017;123:4608‐4616 . © 2017 American Cancer Society . Abstract : Cytogenetic clonal evolution is associated with shorter survival and higher acute myeloid leukemia transformation rates. The presence of subclones indicates a more aggressive phenotype of myelodysplastic syndromes with an adverse prognosis.